Endothelial differentiation of bone marrow mesenchyme stem cells applicable to hypoxia and increased migration through Akt and NFκB signals. Issue 1 (December 2017) - Liu, Cheng; Tsai, An-Ly; Li, Ping-Chia; Huang, Chia-Wei; Wu, Chia-Ching
Abstract Background Bone marrow mesenchymal stem cells (MSCs) and endothelial progenitor cells (EPCs) are used to repair hypoxic or ischemic tissue. However, the underlining mechanism of resistance in the hypoxic microenvironment and the efficacy of migration to the injured tissue are still unknown. The current study aims to understand the hypoxia resistance and migration ability of MSCs during differentiation toward endothelial lineages by biochemical and mechanical stimuli. Method MSCs were harvested from the bone marrow of 6–8-week-old Sprague–Dawley rats. The endothelial growth medium (EGM) was added to MSCs for 3 days to initiate endothelial differentiation. Laminar shear stress was used as the fluid mechanical stimulation. Results Application of EGM facilitated the early endothelial lineage cells (eELCs) to express EPC markers. When treating the hypoxic mimetic desferrioxamine, both MSCs and eELCs showed resistance to hypoxia as compared with the occurrence of apoptosis in rat fibroblasts. The eELCs under hypoxia increased the wound closure and C-X-C chemokine receptor type 4 (CXCR4) gene expression. Although the shear stress promoted eELC maturation and aligned cells parallel to the flow direction, their migration ability was not superior to that of eELCs either under normoxia or hypoxia. The eELCs showed higher protein expressions of CXCR4, phosphorylated Akt (pAkt), and endogenous NFκB and IκBα than MSCs under both normoxia and hypoxia conditions. The potential migratory signals were discovered by inhibiting either Akt or NFκB using specific inhibitors and revealed decreases of wound closure and transmigration ability in eELCs. Conclusion The Akt and NFκB pathways are important to regulate the early endothelial differentiation and its migratory ability under a hypoxic microenvironment.